Holistic Shakespeare : an experiential learning approach - Charlton, Debra (Intellect, 2012)
Shakespeares plays are staples of the classroom. Yet too often they are taught as antiquated works of literature with little reference to their theatrical life and enduringhuman themes. Applying the methodologies of the holistic education model to the study of four Shakespearean playsOthello, The Tempest, A Midsummer Nights Dream, andMeasure for MeasureHolistic Shakespeareoffers lively theater-based activities to complement traditional analytical exercises. In keeping with the aims of holistic education, each play is studied in relation to a particular social or ethical topic addressed in the work. Despite abundant scholarly works in the field of Shakespeare studies, few texts combine analytical and creative learning methodologiesand none before has specifically applied the principles of holistic education to the topic. Accessible to both teachers and learners, this book will be an essential tool for making Shakespeare come to life in the classroom.